Mello and Campos (1974) method adapted for the recovery of cestodes in birds ( Gallus domesticus ) - Silva, Giane Serafim Da; Romera, Daiane Mompean; Prado, Maykon Bichoffi Do; Soares, Vando Edésio; Meireles, Marcelo Vasconcelos [UNESP] (Instituto Biológico, 2016)
The specific diagnosis and evaluation of the intensity of avian helminth infections are essential for efficacy studies and the determination of drug doses targeted to their control. This study evaluated the Mello and Campos method, originally described for parasitological diagnosis in dogs, in the recovery of scolices from cestode parasites of poultry (Gallus domesticus ). A total of 52 naturally infected birds obtained from farms underwent parasitological necropsy using the Mello and Campos method. The method consisted of four steps: content, soaking, scraping and evaluation. The number of scolices recovered per bird ranged from 1 to 4,345, and the highest number of scolices was recovered from material derived from the soaking step. The cestodes species diagnosed were Amoebotaenia cuneata , Choanotaenia infundibulum , Hymenolepis sp., Raillietina tetragona , Raillietina echinobothrida and Raillietina cesticillus . The Mello and Campos method, originally used to test for helminths in dogs, was effective in avian cestode testing because it includes a soaking step, which enables a more efficient recovery of scolices.

O diagnóstico específico e a avaliação da intensidade da infecção helmíntica em aves são fundamentais em estudos de eficácia e determinação de doses de medicamentos direcionados ao seu controle. O presente trabalho avaliou a aplicação e adaptação da metodologia de Mello e Campos, descrita originalmente para diagnóstico parasitológico em cães, na recuperação de escólices de cestódeos parasitos de aves domésticas (Gallus domesticus ). Foram empregadas 52 aves naturalmente infectadas e oriundas de produções rurais, as quais foram submetidas à necropsia parasitológica, adaptando-se a metodologia Mello e Campos. O método consistiu na realização de quatro etapas: conteúdo, imersão, raspado e avaliação. O número de escólices recuperadas por ave variou de 1 a 4.345, e o maior número de escólices foi recuperado do material oriundo da etapa de imersão. As espécies de cestódeos identificadas foram Amoebotaenia cuneata , Choanotaenia infundibulum , Hymenolepis sp., Raillietina tetragona , Raillietina echinobothrida e Raillietina cesticillus . Os resultados foram avaliados estatisticamente, concluindo-se que a metodologia adotada é eficaz para a recuperação de cestódeos de aves, uma vez que possui a etapa de imersão, que permite a recuperação mais eficiente de escólices.
Método Mello e Campos (1974) adaptado para recuperação de cestódeos de aves (Gallus domesticus)
Keywords: Gallus domesticus; birds; cestoda; helminths; Mello and Campos; Gallus domesticus; aves; cestódeos; helmintos; Mello e Campos